Burn Management by Nursing Students at Basrah University-Iraq: Penanganan Luka Bakar oleh Mahasiswa Keperawatan di Universitas Basrah-Irak - Firas A. Jassim (Academia Open, 2024)
Background: In the process of managing burns, especially mass-burn injuries, first aid, and proper initial care are regarded as crucial measures. Improving the standard of burn treatment is largely dependent on the expertise and practical abilities of nursing students working in burn departments.Methodology: 150 students, both male and female, participated in a descriptive cross-sectional study design at Basrah University's College of Nursing to assess their burn management expertise. Data was gathered via a questionnaire with closed-ended questions. The survey is divided into two sections. The first section includes five questions on the students' sociodemographic traits, such as their age, gender, study type, graduation stage, and place of residence. Twenty questions in the second section of the survey ask about students' understanding of burn management. The study employed a standardized 3-point Likert scale with the options YES, NO, and I DON'T KNOW. 150 students were given the completed questionnaire form, which they read and completed. The researchers then collected the completed form. Results: Most of the sample were in the age interval 19-28,22% of the sample were males and 78% were females. The students had good knowledge about burn management. There are highly significant associations between the academic stage and the scores students got. Conclusions: Most of the samples were in the age interval 19-28 years. The students had good knowledge about burn management. There was a highly significant association between the academic stage and the scores the students got. Recommendations: Expand the burn course to enhance students’ knowledge and Introduce a simulation lab about burn management as part of the skill lab. In the College. Highlights: Knowledge of burn management linked to academic stage progress. Most participants were female and aged 19-28 years. Enhance skills with expanded courses. Keywords: Burn management, nursing students, descriptive study, knowledge assessment, Basrah University